Kidney transplantation during mass disasters—from COVID-19 to other catastrophes: a Consensus Statement by the DESCARTES Working Group and Ethics Committee of the ERA. Issue 2 (6th September 2022) - Sever, Mehmet Sukru; Vanholder, Raymond; Oniscu, Gabriel; Abramowicz, Daniel; Van Biesen, Wim; Maggiore, Umberto; Watschinger, Bruno; Mariat, Christophe; Buturovic-Ponikvar, Jadranka; Crespo, Marta; Mjoen, Geir; Heering, Peter; et al.
ABSTRACT: Mass disasters are characterized by a disparity between healthcare demand and supply, which hampers complex therapies like kidney transplantation. Considering the scarcity of publications on previous disasters, we reviewed transplantation practice during the recent coronavirus disease 2019 (COVID-19) pandemic, and dwelled upon this experience to guide transplantation strategies in the future pandemic and non-pandemic catastrophes. We strongly suggest continuing transplantation programs during mass disasters, if medical and logistic operational circumstances are appropriate. Postponing transplantations from living donors and referral of urgent cases to safe regions or hospitals are justified. Specific preventative measures in anticipated disasters (such as vaccination programs during pandemics or evacuation in case of hurricanes or wars) may be useful to minimize risks. Immunosuppressive therapies should consider stratifying risk status and avoiding heavy immune suppression in patients with a low probability of therapeutic success. Discharging patients at the earliest convenience is justified during pandemics, whereas delaying discharge is reasonable in other disasters, if infrastructural damage results in unhygienic living environments for the patients. In the outpatient setting, telemedicine is a useful approach to reduce the patient load to hospitals, to minimize the risk of nosocomial transmission in pandemics and the need for transport in destructive disasters. If it comes down to saving as many lives as possible, some ethical principles may vary in function of disaster circumstances, but elementary ethical rules are non-negotiable. Patient education is essential to minimize disaster-related complications and to allow for an efficient use of healthcare resources.